A few matters of life and death for the physical education professional - Aragón-Vargas, Luis Fernando (2008)
Even though our Physical Education professionals undergo a rather comprehensive training, it may be possible for them not to be aware of several conditions or situations which may threaten the safety, and even the life of those participating in sporting or recreational events under their care. There is, therefore, a real danger that the very professionals responsible to protect the sports person may end up being the ones causing accidents and complications, e.g., exertional rhabdomyolysis, sickling, exertional heat stroke complications when a victim is not quickly and effectively cooled, and accidents from lightning. The purpose of this study was to measure specific knowledge in these four areas of interest. A 14-item, multiple-choice survey was handed out to 300 participants in the University of Costa Rica's XIV Symposium on Exercise and Health Sciences (October, 2007), selected as a convenience sample from approximately 447 registered participants. 46% of them were professionals with university degrees, 43% were physical education students, and 11% did not report their current status. The sample was comprised of 67% males and 33% females. Knowledge level was identified to be very limited; this paper includes key information on the four topics to help the good physical education professionals to be aware of these potential complications, improving safety and the general experience of those under their care.